Association between nasogastric tubes, pneumonia, and clinical outcomes in acute stroke patients. (27th September 2016) - Kalra, Lalit; Hodsoll, John; Irshad, Saddif; Smithard, David; Manawadu, Dulka
Abstract : Objective: To investigate whether nasogastric tubes (NGTs) increase poststroke pneumonia (PSP), mortality, or poor outcomes in nil-by-mouth acute stroke patients. Methods: This study analyzed prespecified outcomes of PSP at 14 days and mortality and function measured by the modified Rankin Scale at 90 days in 1, 217 nil-by-mouth stroke patients at ⩽48 hours of symptom onset in a multicenter randomized controlled trial of preventive antibiotics between April 21, 2008, and May 17, 2014. Generalized mixed models adjusted for age, comorbidities, stroke type and severity, and quality of care were used. No patients were lost to follow-up at 14 days, and 36 (3%) were lost at 90 days. Results: Patients with NGT (298 of 1, 217 [24.4%]) had more severe strokes (median NIH Stroke Scale score 17 vs 14, p = 0.0001) and impaired consciousness (39% vs 28%, p = 0.001). NGT did not increase PSP (43 of 298 [14.4%] vs 80 of 790 [10.1%], adjusted odds ratio [OR] 1.26 [95% confidence interval (CI) 0.78–2.03], p = 0.35) or 14- and 90-day mortality (33 of 298 [11.1%] vs 78 of 790 [9.9%], adjusted OR 1.10 [95% CI 0.67–1.78], p = 0.71; and 79 of 298 [26.5%] vs 152 of 790 [19.2%], adjusted OR 0.95 [95% CI 0.67–1.33], p = 0.75, respectively). Ninety-day modified Rankin Scale score distribution was comparable between groups (adjusted OR 1.14 [95% CI 0.87–1.56], p = 0.08). PSP independently increased 90-day mortality (40 of 123 [32.5%] vs 191 of 965 [19.8%], adjusted OR 1.71 [95% CI 1.11–2.65], p = 0.015) and was not prevented by antibiotics in patients with NGT (adjusted OR 1.1 [95% CI 0.89–1.54], p = 0.16). Conclusions: Early NGT does not increase PSP incidence, mortality, or poor functional outcomes and can be used safely in acute stroke patients.